Characterisation of composite bonded single-strap repairs under fatigue loading. (November 2015) - Moreira, R.D.F.; de Moura, M.F.S.F.; Figueiredo, M.A.V.; Fernandes, R.L.; Gonçalves, J.P.M.
Abstract: High cycle fatigue behaviour of single-strap repairs of carbon–epoxy laminates was analysed experimentally and numerically. Static and fatigue tests were performed under three-point bending loading. The specimens revealing cohesive failure were selected for the sake of numerical model validation. The numerical approach is based on a mixed-mode I+II cohesive zone modelling accounting for quasi-static and fatigue degradation through a unique damage parameter. It was verified that numerical fatigue life prediction is in the range of the fatigue life observed experimentally. In addition to the validation of the numerical model, several numerical analyses were performed in order to assess the influence of loading, geometry and material properties on the fatigue behaviour of single-strap repairs and important conclusions were drawn. Highlights: High-cycle fatigue of single-strap repairs in composites was analysed. A mixed-mode cohesive zone model was used to predict fatigue life of repairs. The model was validated with experimental results on single-strap repairs. The model was then used to assess the effect of several parameters on fatigue life.